Energy management policy / Nurzawani Md Sofwan ... [et al.] - Md Sofwan, Nurzawani; Budin, Hemyza; Abd Rashid, Ahmad Faiz; Mohd Anas Khan, Mohd Yazid; Yusuf, Nur Afisha; Abu Bakar, Nur Ain; Emeih Wahed, Wan Juliana; Bohari, Asmah Alia; Morni, Affidah; Johari, Aiza; Perreau, Madeleine Elna (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
UiTM is committed to managing energy in a responsible manner as part of a global environmental strategy as shown in figure below. While maintaining operational goals and providing a good working and learning environment, UiTM has eﬀectively managed the energy use, and it aims to.